2015
DOI: 10.2298/fupct1501039m
|View full text |Cite
|
Sign up to set email alerts
|

The effect of storage temperature and thermal processing on catechins, procyanidins and total flavonoid stability in commercially available cocoa powders

Abstract: Storage stability of catechin, epicatechin, procyanidins B1-B4 and total flavonoids in cocoa powder samples was studied over the temperature range 4-35?C. Thermal stability of total flavonoids was studied over the temperature range 95-125?C. Total flavonoids concentration decreased as a function of time and the degradation was accelerated at higher temperatures: a half-life (t1/2) of total flavonoids was much shorter at room temperature than during cold storage. A first-order kinetic model fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
1
0
4
Order By: Relevance
“…According to the statement by Dallas et al [ 35 ], procyanidins decreased 5 or 10 times faster at the higher temperatures of 32 and 42 °C. Mrmošanin et al [ 36 ] observed a similar effect in cocoa powders, where the procyanidin concentration decreased as the temperature increased; specifically, the loss was greater than 50% after 30 days at 35 °C. Del-Toro-Sánchez et al [ 37 ] reported a massive 36% reduction in the total phenolic compounds of the herb, Anemopsis californica , extracts stored at 50 °C, 25 °C, and 4 °C for 180 days.…”
Section: Resultsmentioning
confidence: 80%
“…According to the statement by Dallas et al [ 35 ], procyanidins decreased 5 or 10 times faster at the higher temperatures of 32 and 42 °C. Mrmošanin et al [ 36 ] observed a similar effect in cocoa powders, where the procyanidin concentration decreased as the temperature increased; specifically, the loss was greater than 50% after 30 days at 35 °C. Del-Toro-Sánchez et al [ 37 ] reported a massive 36% reduction in the total phenolic compounds of the herb, Anemopsis californica , extracts stored at 50 °C, 25 °C, and 4 °C for 180 days.…”
Section: Resultsmentioning
confidence: 80%
“…Antioksidan merupakan senyawa pemberi elektron (electron donor). Menurut Mrmosanin (2015) beberapa senyawa golongan dari flavonoid bersifat sensitif pada suhu panas dan hal ini berakibat kepada terjadinya degradasi kimia, fisik dan mikrobiologi. Degradasi kimiawi seperti hidrolisis atau oksidasi dapat terjadi seiring dengan meningkatnya temperatur selama proses pemanasan ataupun selama waktu penyimpanan [6].…”
Section: Pendahuluanunclassified
“…Menurut Mrmosanin (2015) beberapa senyawa golongan dari flavonoid bersifat sensitif pada suhu panas dan hal ini berakibat kepada terjadinya degradasi kimia, fisik dan mikrobiologi. Degradasi kimiawi seperti hidrolisis atau oksidasi dapat terjadi seiring dengan meningkatnya temperatur selama proses pemanasan ataupun selama waktu penyimpanan [6]. Selain suhu dan waktu penyimpanan waktu maserasi juga berpengaruh terhadap kandungan antioksidan tersebut [7].…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian diketahui bahwa antioksidan memiliki sensitivitas terhadap suhu panas sehingga dapat menyebabkan senyawa flavonoid tersebut mengalami degradasi kimia sehingga dapat menurunkan aktivitas antioksidan selama proses pemanasan. 15 Suatu bahan dapat dikatakan aktif sebagai antioksidan bila presentase aktivitas antioksidan lebih atau sama dengan 50%. Dari hasil uji aktivitas antioksidan pada semua sampel perlakuan didapatkan bahwa aktivitas antioksidannya kurang dari 50%.…”
Section: Pembahasanunclassified